Postnatal exposure to DINP was associated with greater alterations of lipidomic markers for hepatic steatosis than DEHP in postweaning mice - Yang, Yan; Sun, Fengjiang; Chen, Haojia; Tan, Hongli; Yang, Liu; Zhang, Long; Xie, Jinxin; Sun, Jiachen; Huang, Xiaochen; Huang, Yichao (The Science of the total environment, 2021)
The toxicity of the endocrine disruptor di(2-ethylhexyl) phthalate (DEHP) has been extensively studied for its hormonal dysregulation, obesogenic effect and associated metabolic diseases. DEHP's primary substitute di-isononyl phthalate (DINP), however, although increased in annual production globally, requires better understanding of its health effect. Our previous work reported disruptions in plasma lipid profiles, but the metabolic responses following phthalate exposure in the liver, particularly the entire hepatic lipidome, have been lacking. A targeted lipidomic technique was applied to accurately quantify a total of 363 lipid species in the liver of neonatal mice after exposure to a daily dose of 4.8 mg/kg body weight/day from birth throughout lactation. Distinct patterns of disruption for each sum of lipid classes or sub-classes between the genders were the most noticeable. Following DINP administration, female pups were subject to greater changes in phosphatidylethanolamines, bis(monoacylglycero)phosphate and ceramides. In contrast, the males exhibited less changes in the phosphoglycerol backbone-based molecules, whereas glycerol and cholesterol esters were more disrupted by DINP. DEHP, however, induced less changes overall compared to DINP. These findings highlighted the predominant lipidomic disruption of DINP on glycerol (diacylglycerides and triacylglycerides) and/or cholesterol (in ester or free form) molecules in neonatal mice across genders, suggesting the genesis of hepatic steatosis occurring at as early as post weaning. Collectively, these findings question the suitability of DINP as a safe DEHP substitute and warrant further investigation on longer-term exposure to elucidate its effect on chronic liver diseases. [Display omitted] •Both DINP and DEHP induced gender-specific disruptions in the hepatic lipidome.•Primary lipidomic disruption was on glycerol and cholesterol molecules.•DINP induced disruption in bile acid metabolism by altering liver cholesterol metabolism.•DINP induced more pronounced disruption in liver lipidome than those by DEHP.